The effect of alkali treatment on tensile properties and water absorption of coir / polypropylene biocomposite - Ng, Yik Ru (2017)
Nowadays, natural fiber has play important role as reinforcements for polymer based- composites.The fiber reinforced polymer have been applied in variety of application due to high tensile strength and modulus. In this work, coir fiber were treated with sodium hydroxide solution (3 wt% and 5 wt%) for various times (2. 4 and 6 hours) at room temperature. Then, 10 and 30 wt% of treated fiber with size 160-250 μm were mix with polypropylene to prepare the biocomposite. The influence of alkali treatment time on morphology analysed using scanning electron microscopy (SEM). Thermogravimetric analysis (TGA) used to evaluate thermal stability of treated fiber by observing the weight loss at different temperature to indicate degradation of components. Tensile strength and water absorption of treated coir/ PP biocomposite were studied in this research. The alkali treatment was improved the properties of coir based on chemical composition, morphology and thermal stability. Fiber that treated with alkali treatment was resulted rougher surface due to most of the lignin and pectin was removed. It was determined that 5 wt % NaOH with 6 hour treatment time treated coir fiber reinforced PP composites with 30 wt% fiber loading performed the highest mechanical properties. The tensile strength and tensile modulus measured were 28.74 MPa and 1338.08 MPa respectively. The chemical treatment had reduced the water absorption of biocomposite due to removal hemicellulose component.